O ensino superior privado no Brasil: intercursos entre mercado e monopólio - Martins, Thiago de Melo (2020)
The objective of this work was to analyze the expansion of private higher education in Brazil from the main public / private corporate groups regarding the impacts and demands of their offer between the market, public education policies and social demands. The methodology used in this work focused on the qualitative approach from the specialized literature on the theme and documentary analysis considering five corporations selected for the understanding of the object (Kroton (Cogna), YDUQS (Estácio), Laureate, Unip and Ser Educacional. documentary view of and about corporations, we highlight the following as a search path: a) Analysis of grades of courses offered by the National Institute of Educational Studies and Research Anísio Teixeira (INEP): they as disclosures by Enade and other indexes that believe quality HEI; b) The exponential growth of supply by corporations, through institutional records of free access, the market reached and its relations with public policies and ways of impacting social implications (social inclusion considering the socioeconomic level, among others). As this is a state-of-the-art research, the results of this investigation are possible that the HEIs with for-profit institutions do not fulfill with social responsibilities regarding students with literacy problems, in the case of groups taking them to provide extra support.